Emotif Istimewa Di Balik Lirik Lagu “Terpaut Oleh Waktu” Karya Danilla Riyadi - Annisa Ramadiyanti (Pusat riset dan Inovasi Nasional, 2023)
The purpose of this study is to describe, analyze, and find the style of language contained in song lyrics adrift by the time of one of Danilla Jelita Poetri Riyadi's works in the Telisik Album. In the lyrics of the song Adrift by the time of the album Telisik there are interesting words for the author to study based on his language style. Time adrift means